Slow‐Moving Phase Boundary in Li4/3+xTi5/3O4. Issue 10 (21st August 2021) - Joshi, Yug; Lawitzki, Robert; Schmitz, Guido
Abstract: Lithium titanate is one of the most promising anode materials for high‐power demands but such applications desire a complete understanding of the kinetics of lithium transport. The poor diffusivity of lithium in the completely lithiated and delithiated (pseudo spinel) phases challenges to explain the high‐rate performance. This study aims at clearing the kinetics of lithium transport using an innovative technique that employs optical microscopy in a constrained region of sputter‐deposited thin‐film samples. It enables the in situ observation of the transport of lithium through the electrode. Furthermore, with a thermostatically controlled cell, the Arrhenius‐like temperature dependence is revealed. The quantitative findings demonstrate that indeed the end phases have poor diffusivity which is, however, accelerated at intermediate Li concentrations in the spinel structured Li4/3+ δ Ti5/3 O4 phase. Surprisingly, the slow migration of the phase boundary hinders the formation of the Li‐rich (rock‐salt) phase in the initial stages. Such kinetic control by the phase boundary stands in obvious contrast to a prior (theoretical) study postulating almost "liquid" behavior of the interface. Only after the Li diffusion into the Li‐poor (spinel) phase has faded, when approaching the solubility limit, the further growth of the rock‐salt phase becomes diffusion controlled. Abstract : A novel experimental method unravels temperature dependent diffusion and barrier coefficients for the two phases (Li7/3 Ti5/3 O4 and Li4/3+δ Ti5/3 O4 ) and the phase boundary. Electrode‐size dependent, slow/linear migration of the phase boundary, in the initial stages of lithiation, is observed. This migration is controlled by the concentration gradient in the L4/3+δ Ti5/3 O4 phase formed ahead of the phase boundary.